Surveillance and film - Wise, J. Macgregor (John Macgregor) (New York Bloomsbury Academic, 2016)
"Examines the ways that surveillance has been represented in cinema over the last forty years, especially themes of voyeurism, ethics, trust, and control"--
Machine generated contents note: -- List of images -- Acknowledgements -- Introduction: mapping the surveillant imaginary -- The watchers -- The watched -- Surveillance societies -- Procedurals -- The thrill of the real -- Conclusion: Some must watch.
Includes bibliographical references and index.
Keywords: Electronic surveillance in motion pictures; Voyeurism in motion pictures